Privacy and security policies in big data - Tamane, Sharvari 1973-; Solanki, Vijender Kumar 1980-; Dey, Nilanjan 1984- (IGI Global, Disseminator of Knowledge, 2017)
"This book covers the fundamental concepts of big data management and analytics along with recent research development in big data. It also includes various real time/offline applications and case studies in the field of engineering, computer science, information security, cloud computing with modern tools and technologies used"...
Includes bibliographical references and index
Keywords: Big data -- Security measures; Data protection; Privacy, Right of; Telecommunication policy; Datensicherung; Datenschutz; Big Data; Aufsatzsammlung